Laccases as palladium oxidases. Issue 2 (27th November 2014) - Mekmouche, Yasmina; Schneider, Ludovic; Rousselot-Pailley, Pierre; Faure, Bruno; Simaan, A. Jalila; Bochot, Constance; Réglier, Marius; Tron, Thierry
Abstract : Combining a palladium-based complex with a laccase allows the oxidation of an alcohol substrate at room temperature and atmospheric pressure. Abstract : The first example of a coupled catalytic system involving an enzyme and a palladium(ii ) catalyst competent for the aerobic oxidation of alcohol in mild conditions is described. In the absence of dioxygen, the fungal laccase LAC3 is reduced by a palladium(0) species as evidenced by the UV/VIS and ESR spectra of the enzyme. During the oxidation of veratryl alcohol performed in water, at room temperature and atmospheric pressure, LAC3 regenerates the palladium catalyst, is reduced and catalyzes the four-electron reduction of dioxygen into water with no loss of enzyme activity. The association of a laccase with a water-soluble palladium complex results in a 7-fold increase in the catalytic efficiency of the complex. This is the first step in the design of a family of renewable palladium catalysts for aerobic oxidation.